PENGARUH PENGHINDARAN PAJAK DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN KONTRUKSI DI BEI TAHUN 2018-2019 - Rani Sihotang; Harlyn L. Siagian (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2021)
The main companies goal is to increase the companies value. The companies value and the way companies do increase firm value is by maximizing the company’s capital structure. This study airms to analyze the tax avoidance effect and profitability on the capital structure of construction companies on the Indonesia stock exchange in 2018-2019. In this study, the part of financial performance is the capital structure. The method used in this research is a quantitative method and data processing using the SPSS technique.This research taking data from the annual financial reports of 11 construction companies and the variables in this study are Tax Avoidance (X1), Profitability (X2), and Capital Structure (Y). The method used in analyzing the data is the classical assumption test. Based on this research, there are test results that prove that tax avoidance and capital structure have a significant effect, profitability and capital structure have a significant effect.